Transcriptional Profiling of Monocytes Deficient in Nuclear Orphan Receptors NR4A2 and NR4A3 Reveals Distinct Signalling Roles Related to Antigen Presentation and Viral Response - Phelan, David E.; Shigemura, Masahiko; Aldhafiri, Sarah; Mota, Catarina; Hall, Thomas J.; Sznajder, Jacob I.; Murphy, Evelyn P.; Crean, Daniel; Cummins, Eoin P. (Frontiers in Immunology, 2021)
The nuclear receptor sub-family 4 group A (NR4A) family are early response genes that encode proteins that are activated in several tissues / cells in response to a variety of stressors. The NR4A family comprises NR4A1, NR4A2 and NR4A3 of which NR4A2 and NR4A3 are under researched and poorly understood, particularly in the context of immune cells. NR4A expression is associated with multiple diseases e.g. arthritis and atherosclerosis and the development of NR4A-targetting molecules as therapeutics is a current focus in this research field. Here, we use a combination of RNA-sequencing coupled with strategic bioinformatic analysis to investigate the down-stream effects of NR4A2 and NR4A3 in monocytes and dissect their common and distinct signalling roles. Our data reveals that NR4A2 and NR4A3 depletion has a robust and broad-reaching effect on transcription in both the unstimulated state and in the presence of LPS. Interestingly, many of the genes affected were present in both the unstimulated and stimulated states revealing a previously unappreciated role for the NR4As in unstimulated cells. Strategic clustering and bioinformatic analysis identified both distinct and common transcriptional roles for NR4A2 and NR4A3 in monocytes. NR4A2 notably was linked by both bioinformatic clustering analysis and transcription factor interactome analysis to pathways associated with antigen presentation and regulation of MHC genes. NR4A3 in contrast was more closely linked to pathways associated with viral response. Functional studies further support our data analysis pointing towards preferential / selective roles for NR4A2 in the regulation of antigen processing with common roles for NR4A2 and NR4A3 evident with respect to cell migration. Taken together this study provides novel mechanistic insights into the role of the enigmatic nuclear receptors NR4A2 and NR4A3 in monocytes.